Investigation into the disappearing small stock premium: time varying returns or arbitrage? - Cheah, Chee Yian. (2008)
The objective of this thesis is to investigate the disappearance of an anomaly, the size effect by the mid-1980's, specifically looking at the efficient arbitrage of a narrowly- shared small-cap risk and the time-varying risk and return hypotheses as the two most plausible candidates to explain for the disappearance of the size effect.